(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the most common semen abnormalities and risk factors associated with different types of semen abnormalities in infertile male. Study Design: Cross sectional study Place and Duration of Study: This study was conducted in the Department of Obstetrics and Gynaecology, Unit B, Lady Reading Hospital Peshawar, for a period of one year from 1st January 2009 to 31st December 2009. Materials and Methods: Hundred male patients with abnormal semen analysis were recruited after fulfilling the inclusion criteria. Semi structured Questionnaire was filled and data was collected regarding association of male infertility with common risk factors. Results were expressed in percentages. Descriptive statistics was applied using Microsoft Excel and the frequency and percentages were calculated. Results: Among 100 infertile male patients, 44% patients had asthenospermia, 17% had oligospermia 14% had azoospermia, 13% had pyospermia and 12% had oligoasthenospermia. Drug addiction was (cigarette or cigarette plus THS) observed in 55% (n=55) of patients. Among all participants 46% (n=46) were overweight or obese, In 40% (n=40) infertile males, there were coital problems. Systemic illness was found to be in 34% (n=34) of males with infertility, of all the participants largest number of infertile males were farmers 19% (n=19). Conclusion: Asthenospermia accounted for the frequently associated problem of abnormal semen analysis followed by oligospermia, azoospermia pyospermia and oligoasthenospermia respectively. Cigarette smoking and obesity are the most frequently associated risk factors.